Agrin-Mediated Cardiac Regeneration: Some Open Questions - Bigotti, Maria Giulia; Skeffington, Katie L.; Jones, Ffion P.; Caputo, Massimo; Brancaccio, Andrea (Frontiers in Bioengineering and Biotechnology, 2020)
After cardiac injury, the mammalian adult heart has a very limited capacity to regenerate, due to the inability of fully differentiated cardiomyocytes (CMs) to efficiently proliferate. This has been directly linked to the extracellular matrix (ECM) surrounding and connecting cardiomyocytes, as its increasing rigidity during heart maturation has a crucial impact over the proliferative capacity of CMs. Very recent studies using mouse models have demonstrated how the ECM protein agrin might promote heart regeneration through CMs de-differentiation and proliferation. In maturing CMs, this proteoglycan would act as an inducer of a specific molecular pathway involving ECM receptor(s) within the transmembrane dystrophin-glycoprotein complex (DGC) as well as intracellular Yap, an effector of the Hippo pathway involved in the replication/regeneration program of CMs. According to the mechanism proposed, during mice heart development agrin gets progressively downregulated and ultimately replaced by other ECM proteins eventually leading to loss of proliferation/ regenerative capacity in mature CMs. Although the role played by the agrin-DGC-YAP axis during human heart development remains still largely to be defined, this scenario opens up fascinating and promising therapeutic avenues. Herein, we discuss the currently available relevant information on this system, with a view to explore how the fundamental understanding of the regenerative potential of this cellular program can be translated into therapeutic treatment of injured human hearts.